PEWARISAN NILAI-NILAI AJARAN ISLAM PADA KELUARGA ETNIS MANDAR - Husain Husain; Fathiyah Fathiyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The Mandar community is a society that upholds values, the practice of Mandar culture is identical to the teachings of Islam. This study aims to determine the forms of Islamic teachings and the process of inheritance in the Mandar family. this research is descriptive qualitative research. Data were obtained through interviews with several informants. The results showed that the Mandar community instilled the values ​​of Islamic teachings in the form of prayer, fasting, covering aurat, thahara, consuming halal food, and limiting social interactions. The inheritance pattern is carried out using four methods, namely: giving advice, giving examples, rewards and punishments, and dialogue